Ancient Greece - D'Angour, A (Oxford University Press, 2020)
This chapter outlines the evidence for musical history in ancient Greece, connecting it to philosophical approaches represented by Plato and others, as well as to recently elucidated documents with Ancient Greek musical notation. Ideas of ethos and mimesis are related to what may be known about the sounds of ancient Greek music as elicited from descriptions, surviving scores, and replicas of instruments such as the aulos (double pipe). The chapter seeks to elucidate the notion of mousikē (‘music’, as derived from the name of Greek divinities Mousai, the Muses) in its cultural context, and to connect elements of ancient musical traditions such as metre and harmonics to contemporary aural and musical realities.